Automated keratometry at low cost. - Ventura, L. (IEEE Engineering in medicine and biology magazine)
Describes an automatic optical system that is attached to a slit lamp in order to provide automatic keratometry at low cost. The system consists of projecting a light ring as a target onto the patient's cornea as well as analysis of the deformation of the target in order to obtain the radius of curvature and the axis of the associated astigmatism. The reflected image of the target is displayed on a PC monitor, while dedicated software performs the analysis of the image, which provides the corneal keratometry